Schwannoma maligno do vago - Correia, Bernardes (1995)
Von Recklinghausen neurofibromatosis (neurofibromatosis type 1) is an autosomal dominant disorder that occurs in 1 in 3,000 life births. Malignant degeneration of subcutaneous neurofibroma occurs in about 5 to 10 percent of patients; however, manifestations in the vagus nerve are rare. There are five reported cases of malignant schwannoma of the intrathoracic vagus nerve, and only one was associated with von Recklinghausen neurofibromatosis. We believe that we present the second reported case of a malignant peripheral nerve sheath tumor, involving the vagus nerve in a patient with von Recklinghausen neurofibromatosis.